Characteristics of Socially Isolated Residents in Long-Term Care: A Retrospective Cohort Study - Stephanie A. Chamberlain PhD; Wendy Duggleby PhD, RN; Pamela B. Teaster PhD; Carole A. Estabrooks CM, PhD, RN, FCAHS, FAAN (Gerontology and Geriatric Medicine, 2020)
Objectives: To identify socially isolated long-term care residents and to compare their demographic characteristics, functional status, and health conditions to residents who are not isolated. Methods : We conducted a retrospective cohort study using the Resident Assessment Instrument, Minimum Data Set, 2.0 (RAI-MDS) data, from residents in 34 long-term care homes in Alberta, Canada (2008–2018). Using logistic regression, we compared the characteristics, conditions, and functional status of residents who were socially isolated (no contact with family/friends) and non-socially isolated residents. Results : Socially isolated residents were male, younger, and had a longer length of stay in the home, than non-socially isolated residents. Socially isolated residents lacked social engagement and exhibited signs of depression. Discussion: Socially isolated residents had unique care concerns, including psychiatric disorders, and co-morbid conditions. Our approach, using a single item in an existing data source, has the potential to assist clinicians in screening for socially isolated long-term care residents.